Marknadsundersökning för SCA Skog AB avseende utbor i Mälardalen - Wahlquist, Fredrik (SLU/School for Forest Management, 2009)
The need of raw material does of course fluctuate but the long term view is an increasing demand due to the growing consumption of sawn timber products, pulp, paper and lately also biomass. This has led to a keener competition for wood. At the same time there is an ongoing structural change of a significant part in the Swedish wood supply market, the private forest owners. In 1992, 22 % of Sweden´s 335 000 private forest owner lived apart from their forest. In 2007 this figure had risen to 36 %. SCA Skog acquires a substantial part of its wood consumption from the private sector and distant forest owners constitutes 38 % of all private owned forest properties in northern Sweden. The primary aim of this report is to make a survey of distant foreign owners, with their forests within SCA´s operational district, who has settled in Mälardalen and to outline a future market approach to this group. There are about 2 500 such distant forest owners in this part of the country. All together they own approximately 185 000 hectares of forest representing a vast amount of wood.